RELT Is Upregulated in Breast Cancer and Induces Death in Breast Cancer Cells - Maryann Batiste; Bethany Joy; Cara K. Yee; Luke Cho; Ashley Christensen; Ihab Abed; Kailey Nguyen; Anusri Yanumula; Hannah Chang; Evan D. Cho; Wenjia Wang; Emily Chou; et al. (Biomedicines)
Background: Receptor Expressed in Lymphoid Tissues (RELT) is a TNFRSF member that has two paralogs, RELL1 and RELL2; the three proteins are collectively referred to as RELT family members (RELTfms). Methods: We sought to evaluate RELT expression in cancerous cells by using real-time PCR, western blotting, flow cytometry, and immunohistochemistry (IHC). The mechanism of RELT-induced cell death was assessed by western blotting, flow cytometry, luciferase assays, and morphology staining. RELT localization was detected through immunofluorescence and western blotting, and co-immunoprecipitation was used to test whether a mutated RELT interacts with the OXSR1 kinase. Results: RELT and RELL1 protein expression was significantly elevated in cell lines representing breast and lung cancer, whereas RELL2 protein expression was relatively consistent across different cell lines. The surface expression of RELT was highest in monocytes. IHC staining revealed increased RELT expression in malignant breast cancer biopsies compared to patient-matched benign tissue. RELTfm overexpression induced death in MDA-MB-231 (231) breast cancer cells, accompanied by increased phosphatidylserine externalization and Caspase-3/7 activation. The co-transfection of plasmids predicted to block the phosphorylation of RELT by the OXSR1 kinase did not abrogate RELT-induced apoptosis, indicating that the activation of p38 by RELT through the OXSR1 kinase is not required for RELT-induced cell death. Interestingly, nuclear localization of RELT was detected in 231 and HEK-293 cells. Conclusions: These results demonstrate that RELT induces death in breast cancer cells through an apoptotic pathway that does not require OXSR1 phosphorylation and that RELT possesses the ability to translocate to the nucleus, a novel finding that warrants further investigation.